2014
DOI: 10.1186/1471-2458-14-1259
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, behavioural and cognitive correlates of work-related sitting time in German men and women

Abstract: BackgroundSitting time is ubiquitous for most adults in developed countries and is most prevalent in three domains: in the workplace, during transport and during leisure time. The correlates of prolonged sitting time in workplace settings are not well understood. Therefore, the aim of this study was to examine the gender-specific associations between the socio-demographic, behavioural and cognitive correlates of work-related sitting time.MethodsA cross-sectional sample of working German adults (n = 1515; 747 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
50
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 57 publications
12
50
0
4
Order By: Relevance
“…This concerns the group of farmers from the presented research group as the sitting time on weekdays in their case is 4.4±2.9 and 4.5±3.2 hrs/day at weekends, and these results are close to those for people with sedentary work, e.g. highly educated employees (about 5 hours) [37] and office workers (about 6 hours during a working day) [38]. When taking into consideration the youngest farmers (aged 18-29-7.4±1.0 and 30-39 − 5.1±3.3 hours on weekdays) and those with the highest incomes (3,000-4,499 PLN/Є750-1,124 − 5.7±2.1 and ≥4500 PLN/Є1125 − 6.8±1.5 hours at weekends), the described unfavourable phenomenon is even more prevalent.…”
Section: Discussionsupporting
confidence: 62%
“…This concerns the group of farmers from the presented research group as the sitting time on weekdays in their case is 4.4±2.9 and 4.5±3.2 hrs/day at weekends, and these results are close to those for people with sedentary work, e.g. highly educated employees (about 5 hours) [37] and office workers (about 6 hours during a working day) [38]. When taking into consideration the youngest farmers (aged 18-29-7.4±1.0 and 30-39 − 5.1±3.3 hours on weekdays) and those with the highest incomes (3,000-4,499 PLN/Є750-1,124 − 5.7±2.1 and ≥4500 PLN/Є1125 − 6.8±1.5 hours at weekends), the described unfavourable phenomenon is even more prevalent.…”
Section: Discussionsupporting
confidence: 62%
“…The predictors used for modelling in this study were Gupta et al selected a priori from the questionnaire based on (i) whether they would likely predict time spent sedentary or in physical activity according to previous studies (26,29,30,32,(36)(37)(38), (ii) whether they are commonly available in large epidemiological studies and surveys, and (iii) whether they showed a large relative dispersion between workers in our material. Based on these criteria, we arrived at including self-reported information on age, gender, body mass index (BMI), job type, OST, and OPA.…”
Section: Predictorsmentioning
confidence: 99%
“…Explicit prediction models have been proposed before to predict time spent sedentary and in physical activity (23)(24)(25), but these studies have not developed models for exposures at work, which may show associations with self-reported predictors other than leisure time exposures. A few previous studies have, indeed, developed prediction models for time spent sedentary and in physical activity specifically at work (26)(27)(28)(29)(30). However, they have mainly focused on predicting answers to some self-reported variables by another type of self-reported information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So erfordern insbesondere einfache manuelle Berufe körperlich anstrengende Arbeiten, die meist von Ungelernten oder Geringqualifizierten ausgeübt werden. Besserqualifizierte wie auch Besserverdienende verbringen auf der Arbeit dagegen vergleichsweise mehr Zeit im Sitzen [11]. …”
unclassified